Electroactive polymer tag modified nanosensors for enhanced intracellular ATP detection - Kang, Yi-Ran; Jiao, Yu-Ting; Zhao, Chen-Fei; Zhang, Xin-Wei; Huang, Wei-Hua (Analyst (London), 2024)
ATP plays a crucial role in cell energy supply, so the quantification of intracellular ATP levels is particularly important for understanding many physio-pathological processes. The intracellular quantification of this non-electroactive molecule can be realized using aptamer-modified nanoelectrodes, but is hindered by the limited quantity of modification and electroactive tags on the nanosized electrodes. Herein, we developed a simple but effective electrochemical signal amplification strategy for intracellular ATP detection, which replaces the regular ATP aptamer-linked ferrocene monomer with a polymer, thus greatly magnifying the amounts of electrochemical reporters linked to one chain of the aptamer and enhancing the signals. This ferrocene polymer-ATP aptamer was further immobilized onto Au nanowire electrodes (SiC@C@Au NWEs) to achieve accurate quantification of intracellular ATP in single cells, presenting high electrochemical signal output and high specificity. This work not only provides a powerful tool for quantifying intracellular ATP but also offers a simple and versatile strategy for electrochemical signal amplification in the detection of broader non-electroactive molecules involved in different kinds of intracellular physiological processes. We developed a simple and effective electrochemical signal amplification strategy for intracellular ATP quantification, which replaces the regular ATP aptamer-linked ferrocene monomer to a polymer on electrochemical nanosensors.